Mathematical modeling and computation of real-time problems : an interdisciplinary approach - Kulshrestha, Rakhee; Shekhar, Chandra, 1976-; Jain, Madhu, 1959-; Chakravarthy, Srinivas R., 1953- (Boca Raton, FL : CRC Press, 2021)
"The book covers a broad scope in the areas of statistical science, probability, stochastic processes, fluid dynamics, supply chain, optimization, and applications. It discusses advanced topics and the latest research findings, uses an interdisciplinary approach for real-time systems, offers a platform for integrated research, and identifies the gaps in the field for further research"--
A comparative study of vacation models under various vacation policies : a simulation approach / Srinivas R. Chakravarthy -- Transient analysis of M/M/1 retrial queue with balking, imperfect service and working vacation / Madhu Jain and Sibasish Dhibar -- Finite capacity tandem queueing network with reneging / Chandra Shekhar, Neeraj Kumar, Amit Gupta and Rajesh Kumar Tiwari -- Transient solution of Markov model for fault tolerant system with redundancy / KPS Baghel and Madhu Jain -- Performance analysis of Markov retrial queueing model under admission control F-policy / Rakesh Kumar Meena and Pankaj Kumar -- A study on Geo/G/1 retrial queueing system with starting failure and customer feedback / S. Pavai Madheswari, K.Vasanthamani and P. Suganthi -- Application of optimization and statistical techniques in post-harvest supply chain : a systematic literature survey / Rahul Priyadarshi, Srikanta Routroy, Girish Kant Garg -- Prioritization of barriers for e-waste management in India using best worst method / Shivam Goyal and Vernika Agarwal -- Fuzzy analysis of batch arrival priority queueing system with balking / Anamika Jain, Sonali Thakur, Madhu Jain and Bhoopendra Pachauri -- Application of fuzzy AHP approach for evaluation of sustainable energy sources in India / Santosh Kumar Saraswat, Abhijeet Digalwar and Shyam Sunder Yadav -- Fuzzy based evaluation of optimal service time in DCS using KMeans clustering / Anju Khandelwal and Avanish Kumar -- Solving knapsack problem with genetic algorithm approach / Manish Saraswat and Ramesh Chandra Tripathi -- A difference-cum-exponential type efficient estimator of population mean / Kuldeep Kumar Tiwari, Sandeep Bhougal and Sunil Kumar -- A study of after-effects of Kerala floods using VIIRS-OLS nighttime light data / Pranjal Dave and Sumanta Pasari -- Indian plate motion revealed by GPS observations : preliminary results / Yogendra Sharma, Sumanta Pasari and Neha.
OCLC-licensed vendor bibliographic record.
Keywords: Operations research; Mathematical models; Mathematical optimization; Stochastic processes; MATHEMATICS / Mathematical Analysis